(untitled) (Bangladesh Journal of Neurosurgery, 2024)
Background: Cranioplasty (CP) is a straightforward procedure, it may result in a significant number of complications. These include infections, seizures, intracranial hematomas, and others. Objective: This was a retrospective study on outcome of Cranioplasty. Materials and Methods: This retrospective study included patients who underwent decompressive craniectomy due to traumatic brain injury with raised ICP, acute subdural hematoma, compound comminuted skull fracture & ICH, between January January 2019 to December 2020 at Enam Medical College & Hospital, Savar, Dhaka. Data were collected in pre-designed data collection sheet and were analyzed using computerbased programme statistical package for social science (SPSS) windows version 25. Results: This study showed maximum patients (34.2%) were between 21-30 years age. Majority were male (89.5%) and only 5.9% were female. Overall rate of complications was 10.5%. Among them new onset seizure (n = 4), indrawing of skin through bone gap (n=4), hemorrhage (n=2), infection (n = 1), HCP (n = 1), and exposed implant (n=1). Conclusion: We have found the outcome of cranioplasty was better with titanium mesh plate and screw than conventional fixation of bone with polyglactin, polypropylene suture and titanium miniplate and screw. With polypropylene and polyglactin there is more chance of inward displacement of bone fragment and with miniplate and screw there is still chance of indrawing of bone fragment through the bone gap. Bang. J Neurosurgery 2023; 13(1): 20-23